Motoric cognitive risk: epidemiology of a walking speed-based syndrome to predict dementia - Mullin, Donncha Sean (The University of Edinburgh, 2023)
Dementia is a huge global health challenge without a cure. Identifying the early stages enables the implementation of risk-modifying interventions when they may be most effective. Slow gait speed and self-reported cognitive complaints are among the earliest findings reported in the preclinical stage of dementia. The Motoric Cognitive Risk (MCR) syndrome is a high-risk predementia state combining objective slow gait speed and subjective cognitive complaint in independent, dementia-free individuals. This thesis investigates the association between MCR and dementia using meta-analysis and several epidemiological approaches in a Scottish cohort of community-dwelling older adults. The first study presents a systematic review and meta-analysis of the prognostic ability of MCR. This review also outlined hypotheses regarding the underlying mechanisms of MCR, areas that are explored further in the final chapter of the thesis. It examined longitudinal cohort studies that compared an MCR group to a non-MCR group for any health outcome. A thorough search returned 705 records with 15 cohorts eligible for meta-analysis. The meta-analysis included only health outcomes reported from at least three cohorts and judged satisfactory by our clinical content experts. When a study reported an incompatible effect measure, I contacted authors to request data to allow for our own calculation, or I converted the effect measure where possible and appropriate. The meta-analysis found that participants with MCR were at an increased risk of cognitive impairment (adjusted Hazard Ratio [aHR] 1.76, 95% CI 1.49–2.08; I2 = 24.9%), dementia (aHR 2.12, 1.85–2.42; 33.1%), falls (adjusted relative risk 1.38, 1.15–1.66; 62.1%), and mortality (aHR 1.49, 1.16–1.91; 79.2%). There was considerable heterogeneity in how studies diagnosed MCR, cognitive impairment, and dementia. Our review of the underlying mechanisms of MCR suggested that interactions between MCR, poor brain health, falls, and increased mortality are likely due to a range of biological, psychological, and social mechanisms. A major strength of this systematic review and meta-analysis is the thoroughness of its methodology. The second study of the thesis described the prevalence of MCR and associated factors in the Lothian Birth Cohort 1936 (LBC1936). It was the first time MCR had been derived in a Scottish cohort, so it detailed how MCR was coded and implemented. This study also reported slow gait speed cut-offs for the first time in an older Scottish population. It also assessed the overlap of MCR with three other high-risk states of ageing - Mild Cognitive Impairment (MCI), Prefrailty, and Frailty, thus clarifying the degree of cross-over between these related states. MCR was derived in three waves of the cohort at mean ages of 76.3 years (n = 690), 79.3 years (n = 543) and 82 years (n = 425). MCR prevalence rate ranged from 5.3% to 5.7% across the three waves, a little lower than the global average. Factors associated with MCR in this cohort included age, socioeconomic status, and tests of executive function. There was partial overlap between individuals with MCR and MCI, indicating that these concepts, although derived using similar criteria, capture different cohorts of people. This supports the conceptualisation of MCR as complementary to MCI rather than an alternative. The study highlights the need to explore further the strong association between lower socioeconomic status in early and mid-life with MCR later in life. Building on a key finding from the second study of the thesis, the third study focused on socioeconomic status as a risk factor for MCR. This longitudinal observational study used logistic regression analysis adjusting for important demographic, lifestyle, and health covariates to explore the association between MCR at age 76 years, and years of education and occupational social class, categorised into manual versus non-manual occupations. The final model included 671 participants. Results show that lower socioeconomic status as defined by non-manual versus manual occupation (and not years of education) is associated with a greater than three-fold risk of having MCR later in life (adjusted odds ratio 3.55, 95% CI 1.46–8.74; p = 0.005). Putting this study in context with the literature is difficult as there is a paucity of work focussing on socioeconomic status as a risk factor for MCR. However, having a low socioeconomic status is a widely accepted predictor of ill health generally, and dementia more specifically. Therefore, it is no surprise that it was strongly associated with MCR, which is a high-risk state for dementia. This study highlights a novel risk factor for MCR and offers a hypothesis on underlying mechanisms but concludes by recommending further work to unravel the relationship between lower socioeconomic status and MCR. The fourth study shifted temporarily to focus on identifying dementia in LBC1936, an essential piece of work to allow for the later study of MCR as a predictor of dementia. Previously, the LBC1936 cohort lacked a clinically diagnosed dementia outcome. Our study introduced a novel approach to identifying dementia in cohort studies and reported for the first time the incidence and prevalence of all-cause dementia and its subtypes in the LBC1936. We comprehensively evaluated all participants' electronic health records to identify any indications of cognitive impairment. In addition, we performed in-person clinician assessments whenever a participant's cognition was in doubt. Clinical dementia specialists from Old Age Psychiatry, Neurology, and Geriatrics agreed on a diagnosis of probable dementia, possible dementia, or the absence of dementia, and determined the subtype whenever possible. Of the 865 LBC1936 participants included, 118 (13.6%) had dementia by an average age of approximately 86 years. Dementia was more common with increasing age and in women, and the most common type of dementia was due to Alzheimer disease (49.2%). Self-reported dementia diagnoses were positive in only 17.8% of clinically identified dementia diagnoses. This illustrates the importance of a robust clinical dementia diagnosis instead of relying on self-reported diagnoses. Our work will enable researchers to explore the extensive LBC936 data accumulated over a 16-year period for signals that differentiate participants currently living with dementia from those who are not. This includes my newly derived MCR measure, which brings us to the final study of the thesis. The fifth and final study provided a time-to-event analysis with MCR as the predictor variable and dementia as the outcome of interest. It also explored the various trajectories of participants diagnosed with MCR. It classified a total of 680 community-dwelling participants (mean [SD] age 76.3 [0.8] years) free from dementia into non-MCR or MCR groups. It used Cox proportional hazards methods and competing risk regression to evaluate the risk of developing all-cause dementia in the years following MCR diagnosis. The final model adjusted for potential confounders. Results show that, after 10 years of follow-up, 79 of 680 (11.6%) participants developed dementia. The presence of MCR increased the risk of dementia (aHR 2.34 [1.14 to 4.78, p=0.020]) in this Scottish cohort to a similar extent as in other populations. Individuals with MCR follow similar trajectories to the related predementia syndrome, MCI. This study reinforces that MCR could potentially identify a target group for early interventions of modifiable risk factors for dementia. However, it illustrates the heterogeneous nature of MCR progression and highlights that not all older adults with MCR will follow a similar path. This thesis explores the predementia syndrome MCR through meta-analysis and several epidemiological approaches in the Lothian Birth Cohort 1936. The findings represent a significant advancement in our understanding of MCR prevalence, risk factors, predictive ability, and trajectories. Since there are no effective treatments for dementia, prevention is paramount. By improving our understanding of this high-risk predementia state, this thesis brings us closer to the ultimate goal of intervening early in the lifecourse to reduce the number of people living with dementia.
Keywords: dementia; motoric cognitive risk; slow walk; cognitive impairment; gait; falls; mortality; Alzheimer's disease